2017
DOI: 10.1111/1755-0998.12707
|View full text |Cite
|
Sign up to set email alerts
|

Using in situ hybridization to expand the daily egg production method to new fish species

Abstract: The capacity to reliably identify fish eggs is critical in the application of the daily egg production method (DEPM) to estimate biomass of commercially important species. This application has largely been confined to species that have easily identifiable eggs. Various molecular strategies have been used to extend the DEPM to a broader range of species, with recent approaches like in situ hybridization (ISH) that preserves the integrity of whole eggs, embryos or larvae recommended as a suitable alternative ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Morphological identifications were verified using an in situ hybridization (ISH) molecular technique. This technique uses a horseradish peroxidase (HRP) enzyme conjugated oligonucleotide probe that binds specifically to mitochondrial 16S ribosomal RNA of King George whiting and generates a blue color through oxidization with a HRP reactive substrate (Figure 3; Oxley et al, 2017). The ISH probe was applied to a tissue sample from each larva after the head had been removed to prevent potential contamination of the otoliths.…”
Section: Sample Processingmentioning
confidence: 99%
“…Morphological identifications were verified using an in situ hybridization (ISH) molecular technique. This technique uses a horseradish peroxidase (HRP) enzyme conjugated oligonucleotide probe that binds specifically to mitochondrial 16S ribosomal RNA of King George whiting and generates a blue color through oxidization with a HRP reactive substrate (Figure 3; Oxley et al, 2017). The ISH probe was applied to a tissue sample from each larva after the head had been removed to prevent potential contamination of the otoliths.…”
Section: Sample Processingmentioning
confidence: 99%
“…Morphological identifications were verified using an in situ hybridization (ISH) molecular technique. This technique uses a horseradish peroxidase (HRP) enzyme‐conjugated oligonucleotide probe that binds specifically to mitochondrial 16S ribosomal RNA of King George whiting and generates a blue colour through oxidization with a HRP reactive substrate (Figure 2) (Oxley et al., 2017). The chorion of each "possible" egg was mechanically pierced to expose the embryonic tissue to the molecular probe.…”
Section: Methodsmentioning
confidence: 99%
“…In this issue of Molecular Ecology Resources, Oxley et al. () describe an innovative in situ hybridization ( ISH ) approach that successfully solves this important problem and opens an exciting new avenue to ichthyoplankton analysis that may be widely adopted by both fish ecologists and fisheries managers.…”
mentioning
confidence: 99%
“…The new study by Oxley et al. () presents an elegant solution to this problem. Because Snapper eggs and larvae, like those of many species, can't reliably be identified morphologically, previous DEPM studies relied on morphological identification of eggs that has now been shown to be unreliable (Dias et al., ).…”
mentioning
confidence: 99%